SISTEM ANTRIAN VEHICLE CARGO DALAM KEGIATAN LOADING DAN DISCHARGING - Hendro Kuntohadi; Muhammad Haikal Rifqi Imz; Berlian Badarusman (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT Indonesia Kendaraan Terminal is a subsidiary of PT. Pelabuhan Indonesia II, which was established specifically to serve the cargo vehicle, according to the demand from the automotive industry in Japan. The purpose of this research was to determine the level of utilization or the current flurry of loading and discharging activity in international docks at PT. Indonesia Kendaraan Terminal. By using qualitative methods and queue theory, is clearly visible that the utilization rate at the time of loading activity was 15% (p), 24.23 units / hour (λ), 144.84 units / hour (μ), while the utilization rate at the time of discharging activity by 10% (p), 12.99 units / hour (λ), 125.23 units / hour (μ). Its proves that the current utilization rate of loading and discharging activities in the international docks is low (under-utilized), so it needs to increase vehicle traffic in order to increase the utilization rate.